Staphylococcus petrasii subsp. pragensis subsp. nov., occurring in human clinical material - Švec, Pavel; Bel, Annelies De; Sedláček, Ivo; Petráš, Petr; Gelbíčová, Tereza; Černohlávková, Jitka; Mašlanˇová, Ivana; Cnockaert, Margo; Varbanovová, Ivana; Echahidi, Fedoua; Vandamme, Peter; Pantu Ček, Roman (International journal of systematic and evolutionary microbiology, 2015)
Seven coagulase-negative, oxidase-negative and novobiocin-susceptible staphylococci assigned tentatively as Staphylococcus petrasii were investigated in this study in order to elucidate their taxonomic position. All strains were initially shown to form a genetically homogeneous group separated from remaining species of the genus Staphylococcus by using a repetitive sequence-based PCR fingerprinting with the (GTG)5 primer. Phylogenetic analysis based on 16S rRNA gene, hsp60, rpoB, dnaJ, gap and tuf sequences showed that the group is closely related to Staphylococcus petrasii but separated from the three hitherto known subspecies, S. petrasii subsp. petrasii, S. petrasii subsp. croceilyticus and S. petrasii subsp. jettensis. Further investigation using automated ribotyping, MALDI-TOF mass spectrometry, fatty acid methyl ester analysis, DNA-DNA hybridization and extensive biotyping confirmed that the analysed group represents a novel subspecies within S. petrasii, for which the name Staphylococcus petrasii subsp. pragensis subsp. nov. is proposed. The type strain is NRL/St 12/356(T) ( = CCM 8529(T) = LMG 28327(T)).
Keywords: zastoupení bazí; chaperon hsp60; Oxidoreductases; Chaperonin 60; fylogeneze; RNA, Ribosomal, 16S; Česká republika; mastné kyseliny; Phylogeny; Sequence Analysis, DNA; sekvenční analýza DNA; Nucleic Acid Hybridization; molekulární sekvence - údaje; Fatty Acids; hybridizace nukleových kyselin; oxidoreduktasy; Staphylococcus; Czech Republic; DNA, Bacterial; DNA bakterií; lidé; Genes, Bacterial; Humans; Ribotyping; Base Composition; spektrometrie hmotnostní - ionizace laserem za účasti matrice; RNA ribozomální 16S; Molecular Sequence Data; Spectrometry, Mass, Matrix-Assisted Laser Desorption-Ionization; ribotypizace; bakteriální geny